Hadith #3097 - Sunan al-Nasa'i - Abd'h bin Abd al-Rhym عبدة بن عبد الرحيم بن حسان; Abdullah bin Mubarak عبد الله بن المبارك; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Salmah bin Sulaiman al-Mervazi سلمة بن سليمان المروزي; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث; Umar bin Muhammad bin al-Mnkdr عمر بن محمد بن المنكدر; Wuhayb bin al-Ward وهيب بن الورد (Sunan al-Nasa'i)
: “When the Messenger of Allah died and Abu Bakr was appointed as Khalifah, and some of the Arab’s disbelieved, Umar said: ‘O Abu Bakr! How can you fight the people when the Messenger of Allah said: I have been commanded to fight the people until they say La ilaha illallah (there is none worthy of worship except Allah). Whoever says La ilaha illallah, his life and his property are safe from me, except for its right, and his reckoning will be with Allah?’ Abu Bakr, may Allah be pleased wi
Grade:

Hadith #2501 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Abu Hurairah; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Sami Maula Abi Bakr bin 'Abdur Rahman سمي مولى أبي بكر بن عبد الرحمن بن الحارث; Ubda bin Sulaiman عبدة بن سليمان المروزي; Umar bin Muhammad bin al-Mnkdr عمر بن محمد بن المنكدر; Wahayb bin Khalid bin 'Ajlan al-Bahli وهيب بن خالد بن عجلان الباهلي (Sunan Abi Dawud)
On the day of Hunayn we travelled with the Messenger of Allah (ﷺ) and we journeyed for a long time until the evening came. I attended the prayer along with the Messenger of Allah (ﷺ). A horseman came and said: Messenger of Allah, I went before you and climbed a certain mountain where saw Hawazin all together with their women, cattle, and sheep, having gathered at Hunayn. The Messenger of Allah (ﷺ) smiled and said: That will be the booty of the Muslims tomorrow if Allah wills. He then asked
Grade: Sahih